A highly sensitive fluorimetric protocol based on isoindole formation for determination of gabapentin. Issue 51 (23rd September 2019) - Attia, Tamer Z.; Elnady, Mohamed; Derayea, Sayed M.
Abstract : A new, simple, highly sensitive and selective spectrofluorimetric method was developed for determination of gabapentin through its derivatization with o -phthalaldehyde in the presence of 2-mercaptoethanol. Abstract : A new, simple, highly sensitive and selective spectrofluorimetric method was developed for determination of gabapentin through its derivatization with o -phthalaldehyde in the presence of 2-mercaptoethanol. The resulting product was highly fluorescent and its emission intensity was measured at 431 nm after excitation at 335 nm. The effect of different experimental parameters on the formation and stability of the fluorescent product was carefully studied and optimized. The fluorescence–concentration plot was rectilinear over the range of 25–125 ng mL −1 . The lower detection and quantification limits were 3.4 mL −1 and 11.2 ng mL −1, respectively. The procedure was fully validated according to the guidelines of the International Conference on Harmonization. The proposed method was successfully applied for the determination of the investigated drug in its pharmaceutical capsules and the results were in agreement with those of the reported method, in terms of the accuracy and precision. The low cost of analysis and high sensitivity make the proposed method ideally suited for analysis of the investigated drug in quality control laboratories.